2006
DOI: 10.1021/bm060504a
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Protein-co-PEG Networks as Cell-Adhesive and Proteolytically Degradable Hydrogel Matrixes. Part II:  Biofunctional Characteristics

Abstract: We present here the biological performance in supporting tissue regeneration of hybrid hydrogels consisting of genetically engineered protein polymers that carry specific features of the natural extracellular matrix, cross-linked with reactive poly(ethylene glycol) (PEG). Specifically, the protein polymers contain the cell adhesion motif RGD, which mediates integrin receptor binding, and degradation sites for plasmin and matrix-metalloproteinases, both being proteases implicated in natural matrix remodeling. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
176
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(188 citation statements)
references
References 70 publications
6
176
0
Order By: Relevance
“…A similar bone volume was measured in Group II, but the bone was confined at matrix surface. Reproduced from [285]. [369].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar bone volume was measured in Group II, but the bone was confined at matrix surface. Reproduced from [285]. [369].…”
Section: Resultsmentioning
confidence: 99%
“…The Hubbell group has turned their attention to designing and synthesizing hydrogels that mimic the bi-directional biomolecular interactions that naturally occur between cells and the extracellular matrix (ECM) surrounding them [184,[273][274][275][276][277][278][279][280][281][282][283][284][285]. They have found that signals such as cell adhesion sites, bound growth factors, and cleavage sites for proteolytic activity are essential for cells to be able to remodel the ECM and sustain tissue regeneration.…”
Section: Enzymatically Cleavable Peptide-based Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11] The high water content, biocompatibility, nonfouling properties, and mechanically robust nature of many of these hydrogels has also continued to motivate their investigation. Synthetic polymers such as poly(ethylene glycol) (PEG), poly(vinyl alcohol), poly(N-isoproprylacrylamide), poly(lactic-co-glycolic acid) (PLGA), and copolymers of these and other polymers have provided many useful systems for application in biomedical areas, but are often hindered by their lack of biological activity.…”
Section: Introductionmentioning
confidence: 99%